Floral development and anatomy of pistillate flowers of Lophophytum (Balanophoraceae), with special reference to the embryo sac inversion - Sato, Héctor Arnaldo (2016)
Fil: Sato, Héctor Arnaldo. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.